2007
DOI: 10.1111/j.1532-5415.2007.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Depression Assessment Intervention in Home Health Care

Abstract: TRIAD showed that training nurses to assess for depression using an approach developed in partnership with home healthcare agencies led to appropriate referral and care for depressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 48 publications
3
83
0
2
Order By: Relevance
“…It is clearly demonstrated in the present study that rural and urban elderly differ significantly in the prevalence of depression. It also conforms to the views expressed in some literature that place of residence is an important influencing factor for emergence of the state of depression among the elders [7,11,12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is clearly demonstrated in the present study that rural and urban elderly differ significantly in the prevalence of depression. It also conforms to the views expressed in some literature that place of residence is an important influencing factor for emergence of the state of depression among the elders [7,11,12].…”
Section: Discussionsupporting
confidence: 90%
“…Studies by different authors demonstrated the relationship between prevalence of depression and place of residence [7,11,12]. In some studies, prevalence of depression was common among urban elderly [7,13] while in some other studies rural elderly had relatively higher prevalence of depression [14,15].…”
Section: Diagnostic and Statistical Manual Of Mental Disorders [Dsm Imentioning
confidence: 99%
“…For eksempel når det gjelder alvorlig grad av KOLS viser studier at 90 prosent av pasientene også lider av angst og depresjon og har en lav livskvalitet (20,21). Lignende symptomer og følgetil-stander framkommer i forhold til hjertesvikt og ikke minst hjerneslag (19,39).…”
Section: Alvorlig Sykdom Og Ensomhetunclassified
“…Ensomhet kan vaere en betydelig årsak til angst (14)(15)(16), og kan medføre at noen ønsker mer fysisk hjelp for egentlig å dekke sosiale behov (17). Ellers kan alvorlig sykdom skape angst og utrygghet (18)(19)(20), og syke eldre med moderat til omfattende funksjonssvikt og som bor alene hjemme, er spesielt utsatt (21,22). Sosial isolasjon og ensomhet er et helseproblem i seg selv i form av den lidelse det kan medføre, og det kan føre til redusert helse både fysisk og psykisk (6).…”
Section: Introduksjonunclassified
“…However, the effective implementation of this new screening item will require agency support and complementary training. For example, our research and that of others has demonstrated that nurses often do not directly inquire about symptoms of depression but may depend on their observations (Brown, Raue, Roos, Sheeran, & Bruce, 2010;Bruce et al, 2007). When depression is identified (i.e., positive screens), further evaluation is needed, requiring the availability of either a primary care provider with expertise in managing depression or a mental health care provider.…”
mentioning
confidence: 92%